Efektifitas Therapy Pemaafan untuk Meningkatkan Self Acceptance pada Orang dengan HIV/AIDS (ODHA) - Akmal Budi Satrio; Abdul Muhid (KONSELING: Jurnal Ilmiah Penelitian dan Penerapannya, 2021)
The sexually transmitted disease HIV is currently a concern in the community, due to the lack of education provided about this infectious disease to the community, a new problem arises, namely differences in treatment carried out among the community. So that it has an impact on the physical, psychological and mental conditions of people with HIV / AIDS (PLWHA). HIV / AIDS itself has a very negative contribution to psychological development, such as anger, refusing diagnoses, offers and worse until depression, and finally they reach rock bottom and accept the reality they are experiencing. Purpose: This literature review tries to dig deeper into the effectiveness of forgiveness therapy to increase self-acceptance in PLWHA. Method: A writing method that uses literature review by collecting data from phenomena raised from various sources, both journals, books and references that are relevant to the issues and topics raised. Conclusion: Forgiveness therapy has very good effectiveness as a form of individual intervention with people who have serious problems such as HIV/AIDS.